TRANSFORMASI PERPUSTAKAAN UNIVERSITAS TERBUKA DALAM MEMENUHI KEBUTUHAN INFORMASI MAHASISWA - Pratiwi Anindita Adji; Tamara Adriani Salim (Jurnal IPI (Ikatan Pustakawan Indonesia), 2019)
This study discusses about transformation of Indonesia Open University Library to provide library services for lectures and students, especially students and up to which extent master degree students’ information needs have been fulfilled by Indonesia Open University (UT) digital library. This research uses quantitative approach with descriptive survey method. The result of this research indicates that transformation of UT library has not fully been appropriated by master degree students and information needs have not been fulfilled. Therefore, it is necessary to enhance quantity, quality and ease of access to information source, socialization of information source available at UT digital library and active role of librarians in providing information service.